Київське художнє училище (спогади) - Трохименко, К. (Студії мистецтвознавчі, 2008)
The article is devoted to the activities of Kiev Art School in 1901–1909. In the article, archive materials, memories of a well-known Ukrainian artist K.Trohimenko on his years of studies at Kiev Art School are represented. Kiev Art School was a secondary school subordinate to St. Petersburg Academy of Fine Arts and had three art departments: the department of painting, the department of sculpture, the architectural department and the general education department.